Edukasi Mengenalkan Manfaat Pijat Bayi Untuk Meningkatkan Pengetahuan Ibu Yang Memiliki Bayi Usia 3-12 Bulan Di Desa Semen Kecamatan Semen Kabupaten Kediri - Miftakhur Rohmah; Rizki Fajar Amalia; Sheilla Fadia Pratiwi; Nuraini Wirda Lestari; Enjeles Sri Purnama (Jurnal Pengabdian Bidang Kesehatan, 2023)
Massage for babies and toddlers can be interpreted as a comfortable touch of communication between mother and baby/toddler. Touch is a natural touch for babies and toddlers which can take the form of stroking, massaging or massaging. Baby massage is beneficial for the growth, development and healthy emotional condition of children. The aim of this community service is to increase the knowledge and ability to practice baby massage among mothers who have babies/toddlers to support children's growth and development. This activity is carried out by providing outreach in the form of leaflets and baby massage demonstrations about the benefits and techniques of baby massage. Knowledge measurement is carried out by giving a pretest before counseling and demonstration and a posttest after counseling and demonstration. This counseling was carried out in one of the residents' homes in Semen Village, Kediri Regency, which was attended by 14 mothers who had babies/toddlers. The results of the counseling were obtained before the counseling was given, there were 2 mothers (14.3%) with good knowledge and after the activity there was an increase to 10 mothers (71.4%) with good knowledge. It is hoped that further counseling will focus on providing nutrition for the growth and development of babies/toddlers.